THE INFLUENCE OF COMPETENCY ON EMPLOYEE PERFORMANCE THROUGH ORGANIZATIONAL COMMITMENT IN THE BANGKOK UNITED AGENCY AND BONE BOLANGGO REGENCY POLITICS - Datau, Fatma M.; Rahmisyari, Rahmisyari; Musafir, Musafir (Jurnal Manajemen Dan Bisnis, 2026)
This study aims to analyze and explain the influence of competence on employee performance through organizational commitment at the National Unity and Politics Agency of Bone Bolango Regency. The type of research used is quantitative with a survey method. The unit of analysis used is the individual. The collection of basic data used is a survey, the number of samples in this study is 33 respondents. The analysis method used is SEM PLS. The results of the study indicate that competence (X1) has a positive and insignificant effect on employee performance (Y) at the National Unity and Politics Agency of Bone Bolango Regency, commitment (Z) has a positive and significant effect on employee performance (Y) at the National Unity and Politics Agency of Bone Bolango Regency, competence (X) has a positive and significant effect on commitment (Z) at the National Unity and Politics Agency of Bone Bolango Regency and competence (X) has a positive and significant effect on employee performance (Y) mediating commitment (Z) at the National Unity and Politics Agency of Bone Bolango Regency